Переваги та недоліки комунікації в сучасному інформаційному середовищі - Дмитріченко, А. С. (ХНУРЕ, 2024)
The characterization of modern society as an "information society" has become possible because all social processes are carried out through the exchange of information. In this context, new means and tools for effective communication are emerging, as well as the risks of modern communication in the context of the progress of information technology. The paper is devoted to identifying the advantages and disadvantages of communication in the modern information environment.
Keywords: недоліки комунікації; information society